The Ins and Outs of the Leather Industry in Bangladesh - Manjurul Hossain Reza (Newinera Publisher, 2022)
The leather industry in Bangladesh is growing thanks to the country's expanding economic prosperity. Hides and skins, which are by-products of the meat and meat products sector, are often used as raw materials in the leather business. This research aims to offer a complete picture of Bangladesh's leather industry's performance, products, tanning, investment, and environmental impact. This research focused on the technique that will be utilized to gather sufficient data to support this study, as well as the way by which it will be carried out. This study is based upon the literature survey for exploring particular aspects of the leather industry of Bangladesh. The amount of information extracted from several studies based on the objective is related to Bangladesh's leather industry. This study has given a clear picture of the leather industry of Bangladesh which helps government and leather-oriented organizations to take further steps and decision making. This research was limited to investigate only the industry's performance, products, tanning, investment, and environmental impact. But some other facts affect the leather industry of Bangladesh. The leather industry’s performance has improved over time, but it is still not adequate. This research aims to offer a complete picture of Bangladesh's leather industry's performance, products, tanning, investment, and environmental impact.